Characterizing and Improving WiFi Latency in Large-Scale Operational Networks - Sui, Kaixin; Zhou, Mengyu; Liu, Dapeng; Ma, Minghua; Pei, Dan; Zhao, Youjian; Li, Zimu; Moscibroda, Thomas (2016 International Conference on Mobile Systems, Applications, and Services (MobiSys '16), 2016)
WiFi latency is a key factor impacting the user experience of modern mobile applications, but it has not been well studied at large scale. In this paper, we design and deploy WiFiSeer, a framework to measure and characterize WiFi latency at large scale. WiFiSeer comprises a systematic methodology for modeling the complex relationships between WiFi latency and a diverse set of WiFi performance metrics, device characteristics, and environmental factors. WiFiSeer was deployed on Tsinghua campus to conduct a WiFi latency measurement study of unprecedented scale with more than 47,000 unique user devices. We observe that WiFi latency follows a long tail distribution and the 90th (99th) percentile is around 20 ms (250 ms). Furthermore, our measurement results quantitatively confirm some anecdotal perceptions about impacting factors and disapprove others. We deploy three practical solutions for improving WiFi latency in Tsinghua, and the results show significantly improved WiFi latencies. In particular, over 1,000 devices use our AP selection service based on a predictive WiFi latency model for 2.5 months, and 72% of their latencies are reduced by over half after they re-associate to the suggested APs.